Understanding the role of stromal fibroblasts in cancer progression - Tripathi, Manisha (Landes Bioscience, 2012)
The major cellular components of tumor microenvironment, referred to as the cancer stroma, are composed of cancer-associated fibroblasts that support tumor epithelial growth, invasion and therapeutic resistance. Thus when we speak of developing therapies that address tumor heterogeneity it is not only a matter of different mutations within the tumor epithelia. While individual mutations in the stromal compartment are controversial, the heterogeneity in fibroblastic population in a single tumor is not up for debate. Cooperative interaction among heterotypic fibroblasts and tumor cells contribute to cancer progression. Therefore to tackle solid tumors, we need to understand its complex microenvironment. Here we review some seminal developments in the field of tumor microenvironment, mainly focusing on cancer-associated fibroblast.